PERANAN SLURRY TERHADAP KELANGSUNGAN HIDUP BIBIT KAKAO (Theobroma cacao. L) SAAT PINDAH TANAM KE POLIBAG - Yulistiati Nengsih (Universitas Batanghari Jambi, 2013)
Transplanting cocoa seedlings susceptible to deactivation system is a fast and inexpensive way. However, these systems are vulnerable to the decline in seedling resistance due to stress. Slurry application is an alternative to overcome the stress of cocoa seedlings when transplanting. Experiments have been carried out in the Balai Benih Induk Hortikultura, Muaro Jambi in November 2012 until January 2013. Experiment using a completely randomized design with a treatment composition of slurry (a mixture of soil and water) with the following composition: S0: Without Slurry, S1: Soil Slurry Composition 1 kg + 250 cc water, S2: Soil Slurry Composition 1 kg + 500 cc water, S3 : Soil Slurry Composition 1 kg + 750 cc Water, S4: Soil Slurry Composition 1 kg + 1000 cc Water and S5: Soil Slurry Composition 1 kg + Water 1250 cc. Each treatment was repeated three times. The experimental results showed that the composition of the soil slurry composition with 1 kg + 500 cc water (S2) can reduce the mortality rate of cocoa seedlings when transplanting from the nursery to polybag. But do not differ statistically significantly with other treatments because it is thought to value coefficient variation (CV) is high.Keywords: Water stress, seedling vigor, and cacao